Saddle cycles: Solving rational expectations models featuring limit cycles (or chaos) using perturbation methods - Dana Galizia (Quantitative Economics, 2021)
Unlike linear ones, nonlinear business cycle models can generate sustained fluctuations even in the absence of shocks (e.g., via limit cycles/chaos). A popular approach to solving nonlinear models is perturbation methods. I show that, as typically implemented, these methods are incapable of finding solutions featuring limit cycles or chaos. Fundamentally, solutions are only required not to explode, while standard perturbation algorithms seek solutions that meet the stronger requirement of convergence to the steady state. I propose a modification to standard algorithms that does not impose this overly strong requirement.
Keywords: C63; C68; E37; 330; chaos; computational methods; Dynamic equilibrium economies; limit cycles; nonlinear solution methods